Pengembangan Sistem Pengumpulan Promo E-Commerce Berbasis Website Dengan Menerapkan Teknik Web Scraping Dalam Proses Pengambilan Data Promo - Fegreit Rizda Wibowo; Denny Sagita Rusdianto; Achmad Arwan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Shopping is an important activity in fulfilling everyday human needs. Currently the Indonesian people are changing their behavior in shopping by choosing to transact online rather than conventionally. Online transactions known as e-commerce. The growth of e-commerce in Indonesia is currently very high, judging by the large number of e-commerce available. In this study identified problems in e-commerce where there are many promos available, causing consumers to check e-commerce promos one by one. After observing and surveying the questionnaire in this study, respondents needed a system to collect promos from various e-commerce. Based on these problems, research was conducted to build a system that can provide information related to promos found on e-commerce, the system can collect promos from various e-commerce websites using the web scraping method. The development of this system follows the software development process that starts from the stage of needs analysis, design, implementation, and testing of the system. This system is expected to facilitate consumers in e-commerce promo searches and provide appropriate promo information. The results of unit testing, integrase testing and validation testing produce a 100% valid value. In compatibility testing the results show that the system can run on 8 different types of browsers.